2016
DOI: 10.1186/s12885-016-2792-1
|View full text |Cite
|
Sign up to set email alerts
|

Novel biomarkers that assist in accurate discrimination of squamous cell carcinoma from adenocarcinoma of the lung

Abstract: BackgroundTargeted therapies based on the molecular and histological features of cancer types are becoming standard practice. The most effective regimen in lung cancers is different between squamous cell carcinoma (SCC) and adenocarcinoma (AD). Therefore a precise diagnosis is crucial, but this has been difficult, particularly for poorly differentiated SCC (PDSCC) and AD without a lepidic growth component (non-lepidic AD). Biomarkers enabling a precise diagnosis are therefore urgently needed.MethodsCap Analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 38 publications
3
50
0
1
Order By: Relevance
“…27 Cap analysis of gene expression (CAGE) data of 97 NSCLC tissue specimens from Japanese patients treated at the Juntendo University Hospital were obtained from the DNA Data Bank of Japan (DDBJ) (JGAD00000000070). 26 Differential expression analysis was performed using edgeR. 4 DNA methylation data generated by Illumina (San Diego, California) Infinium 450K methylation array platform from the TCGA lung adenocarcinoma (LUAD) dataset were processed to obtain b values that represent DNA methylation levels.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…27 Cap analysis of gene expression (CAGE) data of 97 NSCLC tissue specimens from Japanese patients treated at the Juntendo University Hospital were obtained from the DNA Data Bank of Japan (DDBJ) (JGAD00000000070). 26 Differential expression analysis was performed using edgeR. 4 DNA methylation data generated by Illumina (San Diego, California) Infinium 450K methylation array platform from the TCGA lung adenocarcinoma (LUAD) dataset were processed to obtain b values that represent DNA methylation levels.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, genomic alterations, mutation profiles, DNA methylation patterns, and transcriptomic changes in NSCLC have been extensively investigated in large cohorts. 2,3,[26][27][28] In parallel, genome and transcriptome analyses of large panels of NSCLC cell lines have been developed and publicly available. [29][30][31] Previous reports relied on cDNA microarray analyses for transcriptional profiling of NSCLC with neuroendocrine differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several markers have been studied for the identification of ADC and SqCC. For example, it has been reported that SPATS2 has a sensitivity and specificity of 67% and 100% for the identification of SqCC, and ST6GALNAC1 has a sensitivity and specificity of 67% and 100% for the identification of ADC when using resected tumor tissue [37]. The utility of these candidate biomarkers still needs to be validated in well-designed, large scale studies.…”
Section: Prospective Future Directionsmentioning
confidence: 99%
“…Their combined revelation is often needed to ensure and validate the diagnosis through the identification of the cancer type. Recent studies have also pointed out new molecules to distinguish lung cancer subtypes, such as beta-arrestin-1 (El-Khoury et al, 2016) or SPATS2 (Takamochi et al, 2016), among a large number of other markers. Many of them were discovered through new "omics"-based technologies and are of interest for diagnosis, prognosis and/or response to treatments while detected with in vitro assays.…”
Section: Introductionmentioning
confidence: 99%